Cultural Differences in Prioritizing Applicant Attributes when Assessing Employment Suitability - WEE, Serena (Institutional Knowledge at Singapore Management University, 2014)
We examined how culture influences perceptions of applicant attributes when assessing employment suitability. In two studies (N = 408), we compared members from a collectivistic society (Singapore) to two samples from individualistic societies (the United States and Australia) on their perceptions of applicant attributes across job contexts. For each job, participants either chose between candidates with different attribute profiles or created ideal candidates by allocating a fixed amount of percentile points across different attributes. More often than Australians, Singaporeans chose the candidate with higher levels of the trait (e.g., openness to experience) uniquely associated with the job (e.g., graphic designer). More so than either Americans or Australians, Singaporeans prioritized having the trait most associated with each job. Members from collectivistic societies may require higher levels of the traits most associated with different jobs than members from individualistic societies, who prefer more well-rounded individuals for each job. As discussed, the study of lay perceptions may have implications for training hiring professionals and managers.